On construction of laser acousto-optical heterodyne interferometers with push-pull measurement of product motions - E. V. Leun (Омский научный вестник)
The article discusses the implementation of a differential pushpull measurement method using a phase interpolator and a phase meter in an acousto-optical (AO) heterodyne laser interferometer of displacements (in future –a laser interferometer). To reduce the noise level in the measuring signal, a phase locked loop system with a small jitter has been introduced. In the first measure at the beginning of the object’s movement due to the high accuracy of the phase meter, so-called «slow precise» measurements with high resolution, up to ≈λ/10000, where λ is the wavelength of the laser radiation. For high-speed object motion the clock of «fast rough» measurements is used when the high-speed phase interpolator is running and the phase meter is locked. This push-pull principle of operation of the laser interferometer improves the dynamic and metrological parameters of object motion measurements.